Perforated Incisional Littre’s Hernia: A Rare Content of a Common Hernia - Al, Kumarappan; S, Norly; Tay, Samuel; C , Vicknesh (IIUM Medical Journal Malaysia, 2016)
Anticipation of complications is of paramount importance for a surgeon. Incisional hernia is a well-known complication for abdominal surgeries. Risk factors such as increasing age, obesity, male gender are well known. Intestinal obstruction, strangulation and perforation are imminent complications of this type of hernia if they become incarcerated. Common contents of a ventral incisional hernia are small bowel, large bowel and omentum. Even though Meckel’s diverticulum is a common gastrointestinal anomaly, it is rarely found to be the content of a hernial sac. A hernia sac containing Meckel’s diverticulum is also known as Littre’s hernia. Only a few cases have been reported in the literature. Thus here we present a case of perforated Meckel’s diverticulum that was entrapped in the ventral incisional hernia.